2014
DOI: 10.1002/ejoc.201403108
|View full text |Cite
|
Sign up to set email alerts
|

Buchwald–Hartwig Reactions of Monohaloflavones

Abstract: Thiol–ene “click” chemistry has emerged as a powerful strategy to construct carbon–heteroatom (CS) bonds, which generally results in the formation of two regioisomers. To this end, the neutral ionic liquid [hmim]Br has been explored as a solvent cum catalyst for the synthesis of linear thioethers from activated and inactivated styrene derivatives or secondary benzyl alcohols and thiols without the requirement of using a metal complex, base, or free radical initiator. Furthermore, detailed mechanistic investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 74 publications
1
15
0
1
Order By: Relevance
“…The synthon 8 and the 1,ω-diaminotacrines 9 – 15 were utilized for formation of the desired 6-Cl-THA-scutellarin hybrids K1383 – K1389 in a Buchwald-Hartwig cross-coupling reaction under catalysis of Pd 2 (dba) 3 + BINAP + NaOtBu in dry toluene [ 47 ]. The final compounds were obtained as yellow powders in yields ranging from 15–88%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthon 8 and the 1,ω-diaminotacrines 9 – 15 were utilized for formation of the desired 6-Cl-THA-scutellarin hybrids K1383 – K1389 in a Buchwald-Hartwig cross-coupling reaction under catalysis of Pd 2 (dba) 3 + BINAP + NaOtBu in dry toluene [ 47 ]. The final compounds were obtained as yellow powders in yields ranging from 15–88%.…”
Section: Resultsmentioning
confidence: 99%
“…To the appropriate N -(6-chloro-1,2,3,4-tetrahydroacridin-9-yl)alkane-1-ω-diamine 9 – 15 (0.3 mmol) dissolved in dry toluene under an inert atmosphere compound 7 (0.26 mmol), palladium complex (0.002 mmol), consisting of Pd 2 (dba) 3 (tri(dibenzylideneacetone)dipalladium (0)), BINAP (2,2′-bis(diphenylphosphino)-1,1′-binaphthyl) and NaO t -Bu, were added [ 47 ]. The reaction mixture was held at 110 °C for 24 h. The solvent was evaporated under the reduced pressure and the residue purified by column chromatography using chloroform:methanol (50:1) as a mobile phase.…”
Section: Methodsmentioning
confidence: 99%
“…To further demonstrate the synthetic potential of the aminobenzylation, the product derived from 2 - bromotoluene, NaN(SiMe 3 ) 2 , and benzaldehydes 1a , 1n , 1q , and 1v were readily converted into valuable 2-aryl-substituted indoline derivatives using a Buchwald–Hartwig amination in 81–90% yield (Fig. 4c ) 50 . N -Substituted 2-arylindoline derivatives are used to treat estrogen-deficiency diseases 51 .…”
Section: Resultsmentioning
confidence: 99%
“…Note that no signals for C2 were observed in the 13 C{ 1 H} NMR spectra of 3a-i, probably due to overlaps with other signals. The free rotation of the C2-C10 bond in the last step of the reaction mechanism, as proposed by Kónya et al, 35 allows formation of E and Z isomers. The transformation into the thione increases the rotational freedom and the E isomer is exclusively obtained in the case of 4a.…”
Section: Methodsmentioning
confidence: 93%
“…However, recently Patonay et al identified the ring contraction to the aurone structure based on 2D NMR spectroscopy through comparison with a synthesized 3-aminoflavone. 35 In the molecular structure of 3a, an intramolecular hydrogen bond between the amine functionality and the carbonyl of the benzofuranone moiety is evident, yielding a thermodynamically stable 6-membered ring. The bond length C2-C10 is significantly shorter in 3a (1.372(3) Å) than in 4a (1.403(2) Å) and indicates the presence of an exocyclic double bond in 3a.…”
Section: Methodsmentioning
confidence: 99%